Exploration of Trends in Religious Moderation Values in Islamic Boarding Schools: A Systematic Literature Review - Asy'arie, Bima Fandi; Muttaqin, Amirul; Mustofa, Moh. Aly (Borneo Journal of Islamic Education, 2024)
Abstract This research aims to determine and analyze the concept of Religious Moderation values ​​in the Islamic Boarding School environment and how these values ​​are applied in the practice of life at the Islamic Boarding School. School. In addition, this article focuses on the research period (2020-2024, especially field research at IBS, by obtaining 27 article documents. This research is a type of “systematic literature review” (SLR) methodology with a qualitative approach. “Google Scholar” and “ScienceDirect”. We then performed a bibliometric analysis to understand the bibliographic landscape in this research topic area through “Publish or Perish” (PoP), which was imported into the application “VOSviever.” The findings of trends in religious moderation values ​​in Islamic boarding schools include: (1) tasamuh (tolerance), (2) tawazun (balance), (3) i’tidal (justice). (4) musawah (equality), (5) tahaddur (civilized), (6) syura (deliberation), (7) qudwah (leadership), (8) ishlah (reform), (9) qudwah (pioneering), (10) muwathanah (love for the homeland), (11) al- la’unf (without violence), (12) i’tiraf al-‘urf (culture friendly), and (13) tatawwur wa ibtikar (dynamic and innovative). All of these values ​​are applied in life practices to strengthen the main indicators to create the values ​​of (1) national commitment, (2) non-violence, (3) tolerance, and (4) acceptance of local traditions. Apart from that, Islamic boarding schools also teach openness to local traditions as long as they do not conflict with Islamic values to create a balance between religious teachings and local wisdom. Keywords: religious moderation, Islamic boarding schools, Islamic religious teachings, local traditions.